Kenya's 2017 elections: winner-takes-all politics as usual?. Issue 2 (3rd April 2019) - Cheeseman, Nic; Kanyinga, Karuti; Lynch, Gabrielle; Ruteere, Mutuma; Willis, Justin
ABSTRACT: This article asks what Kenya's 2017 general elections tell us about the capacity of a new constitution to reduce the stakes of political competition and prospects of political instability. Three constitutional changes are particularly important: the adoption of a 50% + 1 threshold for the presidential election; the devolution of power to 47 county governments; and the introduction of a Supreme Court with the right to hear presidential electoral petitions. We find that the impact of the 2010 constitution has been mixed. The 50% plus 1 threshold encouraged coalition formation, but this dynamic has long been evident. Devolution has given a wider set of Kenyans a stake in the system, but has also created new structures that can be used to channel dissent against the state. The Supreme Court demonstrated its capacity to act as an independent institution, but did little to sustain electoral legitimacy. Indeed, while the 2010 constitution has clearly reshaped the political landscape, it was a personal deal that ended the post-election impasse. The elections therefore demonstrate how formal institutions alone cannot change political logics and reveal the continued significance of individual politicians and informal institutions that may compete with or complement their formal counterparts.